BERRYA ROXB. and CARPODIPTERA GRIS. - a. j. g. h. kostermans (Reinwardtia, 1969)
In his monographic treatment of Tiliaceae, Burret {in Notizbl. bot. Gart. Berlin 9: 607. 1926) pointed out the close affinity of Berrya and Carpodiptera, the former represented in Asia and the Pacific area, the latter from Africa and America.